Sustainability of a Moodle-Based Learning Management System (LMS) Based on Post-graduate Students’ Perspectives - Hablil Warid; Lailatul Musyarofah; Kani Sulam Taufik (Budapest International Research and Critics University, 2022)
Moodle is an open-source Learning Management System (LMS) that is gaining popularity in STKIP PGRI Sidoarjo's educational institution. While the education department has accepted Moodle, successfully implementing it for post-graduate students at STKIP PGRI Sidoarjo would then require student acceptance. However, the LMS is the ideal approach for increasing students’ commitment to educational content such as sustainability. The findings indicated that students’ desire to use LMS SIDALACE, Sidoarjo Learning Space, had a beneficial effect on learning as sustainability engagement during the COVID-19 pandemic. Additionally, students perceived closeness, peer references, and subjective well-being are positively associated with perceived ease of use and perceived usefulness, which influences students’ intentions to use, which in turn influences LMS usage for student engagement during Covid-19.